Kekuatan Pembuktian dan Penilaian Alat Bukti Visum Et Repertum dalam Tindak Pidana Pembunuhan Berencana - Narulita Anggun (Verstek, 2019)
The purpose of this research is to fnd of the function Visum et Repertum a proof for gener and to fal attourney and to fnd opinion of The trial judge country in the fnish case premeditaded murder in verdict number; 416/Pid.B/2015/PN.Stb.      Method of the research is Research Normative Law a prespektif. Resources material of law use for primary legal material and secondary law material. Case approach with study literature was the method used in this research.     Based on the results of research conducted by the authors, obtained the result that the evidentiaryefforts made by the Public Prosecutor on the basis of Visum et Repertum in murder case is considered as valid evidence, because Visum et Repertum in written form made by authorized offcials based on his knowledge and signed under oath of offce, thus becoming an authentic deed which automatically becomes a valid evidence and has a value of evidentiary power but must be linked with other evidencesin order to create a material truth. The judge in dropping a verdict has obtained confdence based on at least two valid evidences. The judge also used the Visum et Repertum as a consideration and considered that there was a supportive link between the result of the examination of the Visum et Repertum and the crime committed so that the Judge stated that the Defendant was found guilty of a crime and sentenced to a criminal sentence.Keywords : Visum et Repertum, Proof , Criminal Procedure Law